Angry breathing: a prospective study of hostility and lung function in the Normative Aging Study. Issue 10 (1st September 2006) - Kubzansky, L D; Sparrow, D; Jackson, B; Cohen, S; Weiss, S T; Wright, R J
Abstract : Background: Hostility and anger are risk factors for, or co-occur with, many health problems of older adults such as cardiovascular diseases, all-cause mortality, and asthma. Evidence that negative emotions are associated with chronic airways obstruction suggests a possible role for hostility in the maintenance and decline of pulmonary function. This study tests the hypothesis that hostility contributes to a faster rate of decline in lung function in older adults. Methods: A prospective examination was undertaken of the effect of hostility on change in lung function over time. Data are from the VA Normative Aging Study, an ongoing cohort of older men. Hostility was measured in 1986 in 670 men who also had an average of three pulmonary function examinations obtained over an average of 8.2 years of follow up. Hostility was ascertained using the 50-item MMPI based Cook-Medley Hostility Scale. Pulmonary function was assessed using spirometric tests to obtain measures of forced expiratory volume in 1 second (FEV1 ) and forced vital capacity (FVC). Results: Baseline pulmonary function differed between high and medium/low hostility groups (mean (SE) percent predicted FEV1 88.9 (18.5) v 95.3 (16.9) and FVC 92.5 (16.5) v 98.9 (15.9), respectively; p<0.01 for both). This overall association between higher hostility and reduced lung function remained significant after adjusting for smoking and education, although the effect size was attenuated for both FEV1 and FVC. Higher hostility was associated with a more rapid decline in lung function, and this effect was unchanged and remained significant for FEV1 in multivariate models but was attenuated for FVC. Each standard deviation increase in hostility was associated with a loss in FEV1 of approximately 9 ml/year. Conclusions: This study is one of the first to show prospectively that hostility is associated with poorer pulmonary function and more rapid rates of decline among older men.